TANTRIC SYMBOLISM AND ITS RELEVANCE IN HINDUISM: A STUDY OF CANDI SUKUH ON MOUNT LAWU - Sulastri; Marsono (UHN I Gusti Bagus Sugriwa Denpasar, 2025)
Candi Sukuh, located on the slopes of Mount Lawu, is a late Majapahit monument that prominently displays Tantric symbolism. Its terraced pyramid architecture, lingga–yoni reliefs, and erotic iconography reveal the dominance of Tantric teachings in the candi’s cosmological narrative. This study aims to examine the relevance of Tantra in Hinduism as embodied in the architecture, iconography, and symbolism of Candi Sukuh, while also uncovering its contribution to the enrichment of Hindu philosophy in the Indonesian archipelago. The method employed is qualitative-descriptive analysis with a literature review approach, utilizing studies in archaeology, history of religion, and Hindu philosophy. Data are drawn from journals, books, and prior research on Tantra and Candi Sukuh. The analysis indicates that the candi’s symbols are not merely erotic but represent the unity of body, cosmos, and spirit. The lingga–yoni reliefs emphasize the balance of masculine–feminine energies (Śiva–Śakti) sustaining the cosmos, where sexuality is understood as a sacred power leading toward mokṣa. The findings affirm Candi Sukuh as both a symbolic text and a philosophical heritage enriching the dynamics of Hindu thought in Java.